Safety evaluation of discontinuous lane design of intersection approach in China. Issue 4 (4th July 2019) - Li, Maosheng; Chen, Linli; Chang, Fangrong; Huang, Helai
ABSTRACT: A special kind of road marking design denoted as discontinuous lane design is prevailing in most cities of China, in which a changeover portion between the upstream road segment and the approach of intersection is void of road markings. This article evaluates the road safety and traffic efficiency of the discontinuous lane design for the most typical case that three lanes upstream are followed by four approaching lanes to the intersection. A safety risk comparison was made between the discontinuous lane design and its counterpart continuous lane design by index of postencroachment time (PET). Then, using an ordered probit model, the PETs, representing the severity of traffic conflict, were linked to relevant variables including the traffic volume, the queue length of target lane on the approach, the queue length of the neighboring target lane, the upstream lane used by the vehicle, the vehicle speed before entering the discontinuous zone, and so on. It was found that the upstream lane has an important effect on traffic safety under discontinuous lane design. Continuous lane design is only recommended for intersection approaches with relatively stable right and left turning flows, and not appropriate for specific cases when the turning flows fluctuate significantly in daily periods.